Pendidikan Agama Islam Berperspektif Multikultural (Studi di Sekolah Dasar Tumbuh 1 Yogyakarta) - Willi Ashadi (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
AbstractThis study aims to describe the practice of multicultural Islamic religious education in SD Tumbuh 1 Yogyakarta and its output on the establishment of inclusive and tolerant attitude among students. The results of this study show that the model of learning of Islamic religious education in SD Tumbuh 1 Yogyakarta is inclusive and multicultural. The material of Islamic religious education in SD Tumbuh 1 Yogyakarta emphasizes on universal Islamic values (rahmatān lil 'alamīn). In terms of teaching and learning methods, Islamic religious education teachers are not only fixated on one method, but incorporate various methods. Similarly, the use of media of learning is quite diverse. The evaluation is not only based on cognitive aspect, but also affective and psychomotor aspects. The learning output of Islamic religious education in SD Tumbuh 1 Yogyakarta is able to create student's inclusive thinking. They are very appreciative and tolerant towards other faiths. Keywords: Islamic Religious Education, Multicultural, Inclusive, Tolerant. AbstrakPenelitian ini bertujuan mendeskripsikan praktik pendidikan agama Islam berperspektif multikultural di SD Tumbuh 1 Yogyakarta dan output-nya terhadap pembentukan sikap inklusif dan toleran di kalangan siswa. Hasil penelitian ini menunjukkan bahwa model pembelajaran pendidikan agama Islam di SD Tumbuh 1 Yogyakarta bercorak inklusif dan multikulturalis. Materi pendidikan agama Islam di SD Tumbuh 1 Yogyakarta lebih banyak menekankan nilai-nilai Islam yang universal (rahmatān lil ‘alamīn). Dari sisi metode pengajaran dan pembelajaran, guru pendidikan agama Islam tidak hanya terpaku pada satu metode saja, namun menggabungkan beragam metode. Demikian juga dengan penggunaan media pembelajaran yang cukup beragam. Sementara dari sisi evaluasi, tidak hanya didasarkan pada aspek kognitif semata, namun juga mencakup aspek afektif dan psikomotorik. Output pembelajaran pendidikan agama Islam di SD Tumbuh 1 Yogyakarta mampu membentuk pola pikir inklusif siswa. Siswa sangat apresiatif dan toleran terhadap pemeluk agama lain. Kata kunci: Pendidikan Agama Islam, Multikultural, Inklusif, Toleran.